The benefit of atrial septal defect closure in the elderly patients. (25th November 2020) - Prochownik, P.J; Przewlocki, T; Sobien, B; Gancarczyk, U; Olszowska, M; Podolec, P; Komar, M
Abstract: Objective: Closure of the atrial septal defect in the elderly patients is controversial. The aim of the study was to evaluate the outcomes of transcatheter closure of secundum atrial septal defect (ASD) in elderly patients. Methods: From a total of 650 pts with ASD who underwent transcatheter closure 120 pts over 60 years (70 F, 50 M) with a mean age of 66.7±18.1 (60–78) were analyzed. All patients had an isolated secundum ASD with a mean Qp:Qs: 2.79±1.8 (1.5–3.9). A symptom-limited treadmill exercise tests with respiratory gas exchange analysis and transthoracic color Doppler echocardiographic study as well as Quality of life (QoL) measured using the SF36 questionnaire (SF36q) were repeated in all pts before procedure and after 12 months of follow-up. Results: The device was successfully implanted in all pts (procedure time 30.1±9.9 (10–59) minutes, fluoroscopy time 10.1±7.2 (6–40) minutes). There were no major complications. The defect echo diameter was 19.5±15.4 (12 - 34) mm. The mean balloon stretched diameter of ASD was 22.0±7.8 (14 - 36) mm. The diameter of the implanted devices ranged 16 - 38 mm. After 12 months of ASD closure, all the pts showed a significant improvement of exercise capacity parameters. Seven QoL parameters (except mental health) improved at 12 months follow up compared to their baseline data. The mean SF36q scale increased significantly in 96 (80.2%) pts of mean 41.6±26.1 (4–71). The right ventricular dimension decreased in 101 pts (84.2%) (Table 1). Conclusions: Closure of ASD in elderly patients caused a significant clinical and hemodynamic improvement after percutaneous treatment, which is maintained to long-term follow-up what justified this procedure in old age. Funding Acknowledgement: Type of funding source: None